DESAIN MODEL KLASIFIKASI SAMPAH ORGANIK MENJADI BAHAN BAKU BRIKET BIOMASSA MENGGUNAKAN METODE DEEP LEARNING - Norbertus Tri Suswanto Saptadi; Phie Chyan; Valentina Marchella Widjaja (JURNAL INFORMATIKA DAN KOMPUTER, 2022)
The development of information technology in Makassar has implemented the smart city concept. The mission of urban development is to build the economy of urban communities that have superior capacity, competitiveness, productivity, creativity, innovation, efficiency and use information technology to utilize the waste generated by the community and companies. Cities have problems stemming from development by producing waste in the form of organic and inorganic waste. To empower the community, city governance is needed with a design concept that continues towards green technology. The aim of the research is to design a model that can sort and identify waste based on various types of organic matter that can be used as raw material for making biomass briquettes as a renewable alternative energy source. Research uses deep learning methods as part of machine learning in solving object detection problems in digital image classification in computer vision. The research resulted in a classification model design based on object detection by classifying 5 types of organic waste.